2019
DOI: 10.25159/1998-8125/5679
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of service quality and its measurement for private higher education institutions

Abstract: The strategic importance of service excellence for service industries places the focus on service quality leadership, service quality management systems, service quality dimensions and the measurement of service quality. Many businesses such as private higher education institutions (PHEIs) regard service quality excellence as the single most important and distinct competence for survival and sustainability. The paucity of literature on the topic does not reflect the substantial growth of PHEIs in South Africa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…For the purpose of this article, service quality in PHE is defined as 'meeting and exceeding students' expectations and perceptions by constantly rendering a reliable service that conforms to pre-determined requirements for which the student is willing to pay, resulting in tangible and intangible benefits'. Soni and Govender (2018) referred to the work of Wang (2012) and Dirkse van Schalkwyk and Steenkamp (2014) on the role that service quality plays in South African HEIs, with Vivek et al (2019) who supported their argument by reflecting on Indian HEIs. The studies by Soni and Govender (2018), Marimon et al (2019), Kruja et al (2021), andParasuraman et al (1985) among others, to determine the dimensions of SQ in HEIs have identified different variations.…”
Section: Service Qualitymentioning
confidence: 99%
“…For the purpose of this article, service quality in PHE is defined as 'meeting and exceeding students' expectations and perceptions by constantly rendering a reliable service that conforms to pre-determined requirements for which the student is willing to pay, resulting in tangible and intangible benefits'. Soni and Govender (2018) referred to the work of Wang (2012) and Dirkse van Schalkwyk and Steenkamp (2014) on the role that service quality plays in South African HEIs, with Vivek et al (2019) who supported their argument by reflecting on Indian HEIs. The studies by Soni and Govender (2018), Marimon et al (2019), Kruja et al (2021), andParasuraman et al (1985) among others, to determine the dimensions of SQ in HEIs have identified different variations.…”
Section: Service Qualitymentioning
confidence: 99%
“…Có thể khẳng định rằng thang đo này phù hợp với mọi loại hình dịch vụ vì tính hợp lệ và độ tin cậy của nó [26], [27]. Hơn nữa, có rất nhiều lợi ích của việc sử dụng SERVQUAL đã được chỉ ra và sau đó, nó đã được chấp nhận như một thang đo tiêu chuẩn để đánh giá các khía cạnh khác biệt của chất lượng dịch vụ [38].…”
Section: Chất Lượng Dịch Vụ Thuế Của Cơ Quan Thuếunclassified
“…The majority of studies on higher education service quality in South Africa in the past decade focused on "gap" analyses, using the SERVQUAL scale (Veerasamy et al, 2012;Green, 2014;Naidoo, 2014;Van Schalkwyk & Steenkamp, 2014) and only one used the SERVPERF model (Diedericks, 2012). With the exception of the study by Radder and Han (2009, p. 116), no analyses were undertaken using cluster or predictive analyses techniques to determine statistically, whether there are specific factors that could predict higher education service quality.…”
Section: Introductionmentioning
confidence: 99%